Extensive load of somatic CNVs in the human placenta - Kasak, Laura (Sci Rep, 2015)
Placenta is a temporary, but indispensable organ in mammalian pregnancy. From its basic nature, it exhibits highly invasive tumour-like properties facilitating effective implantation through trophoblast cell proliferation and migration, and a critical role in pregnancy success. We hypothesized that similarly to cancer, somatic genomic rearrangements are promoted in the support of placental function. Here we present the first profiling of copy number variations (CNVs) in human placental genomes, showing an extensive load of somatic CNVs, especially duplications and suggesting that this phenomenon may be critical for normal gestation. Placental somatic CNVs were significantly enriched in genes involved in cell adhesion, immunity, embryonic development and cell cycle. Overrepresentation of imprinted genes in somatic duplications suggests that amplified gene copies may represent an alternative mechanism to support parent-of-origin specific gene expression. Placentas from pregnancy complications exhibited significantly altered CNV profile compared to normal gestations, indicative to the clinical implications of the study.